Very small embryonic-like stem cells (VSELs) on the way for potential applications in regenerative medicine - Thetchinamoorthy, Kannathasan; Jarczak, Justyna; Kieszek, Patrycja; Wierzbicka, Diana; Ratajczak, Janina; Kucia, Magdalena; Ratajczak, Mariusz Z. (Frontiers in Bioengineering and Biotechnology, 2025)
Evidence has accumulated that adult tissues contain a population of early development stem cells capable of differentiating across germ layers into various types of cells. Our group purified these rare cells, naming them very small embryonic-like stem cells (VSELs). With their broad differentiation potential, VSELs have emerged as a new candidate population for clinical applications. This advancement is now possible due to our recent development of a model for ex vivo expansion of these rare cells. Importantly, no evidence suggests that VSELs, isolated from adult tissues, can form teratomas. In this review paper, we update current research on these cells reported in our laboratory as well as in those of several independent investigators.